Developments in surface contamination and cleaning Volume four, - Kohli, Rajiv, 1947-; Mittal, K. L., 1945- (William Andrew, 2012)
In this series Rajiv Kohli and Kash Mittal have brought together the work of experts from different industry sectors and backgrounds to provide a state-of-the-art survey and best-practice guidance for scientists and engineers engaged in surface cleaning or handling the consequences of surface contamination. The expert contributions in this volume cover important fundamental aspects of surface contamination that are key to understanding the behavior of specific types of contaminants. This understanding is essential to develop preventative and mitigation methods for contamination cont.
Keywords: Surfaces (Technology) -- Inspection.; Surface contamination -- Prevention.; Cleaning.; Coatings.; Dust control.; elektronické knihy; electronic books